Impact of Water Quality, Sanitation, Handwashing, and Nutritional Interventions on Enteric Infections in Rural Zimbabwe: The Sanitation Hygiene Infant Nutrition Efficacy (SHINE) Trial. (20th April 2019) - Rogawski McQuade, Elizabeth T; Platts-Mills, James A; Gratz, Jean; Zhang, Jixian; Moulton, Lawrence H; Mutasa, Kuda; Majo, Florence D; Tavengwa, Naume; Ntozini, Robert; Prendergast, Andrew J; Humphrey, Jean H; Liu, Jie; et al.
Abstract: Background: We assessed the impact of water, sanitation, and hygiene (WASH) and infant and young child feeding (IYCF) interventions on enteric infections in the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) trial in rural Zimbabwe. Methods: We tested stool samples collected at 1, 3, 6, and 12 months of age and during diarrhea using quantitative molecular diagnostics for 29 pathogens. We estimated the effects of the WASH, IYCF, and combined WASH + IYCF interventions on individual enteropathogen prevalence and quantity, total numbers of pathogens detected, and incidence of pathogen-attributable diarrhea. Results: WASH interventions decreased the number of parasites detected (difference in number compared to non-WASH arms, –0.07 [95% confidence interval, –.14 to –.02]), but had no statistically significant effects on bacteria, viruses, or the prevalence and quantity of individual enteropathogens after accounting for multiple comparisons. IYCF interventions had no significant effects on individual or total enteropathogens. Neither intervention had significant effects on pathogen-attributable diarrhea. Conclusions: The WASH interventions implemented in SHINE (improved pit latrine, hand-washing stations, liquid soap, point-of-use water chlorination, and clean play space) did not prevent enteric infections. Transformative WASH interventions are needed that are more efficacious in interrupting fecal–oral microbial transmission in children living in highly contaminated environments. Abstract : The water, sanitation, and hygiene and infant and young child feeding interventions tested in the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) trial in rural Zimbabwe had no effects on enteric infections or pathogen-specific causes of diarrhea.